Some Evidence for an Association Between Early Life Adversity and Decision Urgency - Knowles, Johanne P.; Evans, Nathan J.; Burke, Darren (Frontiers in Psychology, 2019)
The relationship between early life adversity and adult outcomes is traditionally investigated relative to risk and protective factors (e.g., resilience, cognitive appraisal), and poor self-control or decision-making. However, life history theory suggests this relationship may be adaptive – underpinned by mechanisms that use early environmental cues to alter the developmental trajectory towards more urgent, short-term strategies. This “urgency” has some theoretical overlap with the most common process models of decision making – evidence accumulation models – which model “urgency” as a decision threshold. The current study examined the relationship between decision urgency (through the linear ballistic accumulator) and early life adversity. A mixture of analysis methods, including a joint model analysis designed to explicitly account for uncertainty in estimated decision urgency values, revealed weak-to-moderate evidence in favour of a relationship between decision urgency and early life adversity, suggesting a possible effect of life history strategy on very basic decision making.